Investigating Moisture-Induced Particle Behavior in a Horizontal Shaft Mixer - Minkyung Sim; Kwang Kim (Fluids)
Grains stored in silos and pellets for injection molding deteriorate in quality due to increased moisture in the particles when exposed to air for a long period of time, so it is necessary to reduce the moisture in the particles through the mixing process. However, few studies have conducted parallel experiments and simulations to understand the behavior of particles depending on their moisture content. In this study, mixing experiments were conducted using superabsorbent polymer (SAP) beads that expand depending on the moisture content, and the interparticle friction coefficient and interface friction coefficient required for simulation were derived. As a result, it was found that moisture generates an adhesive force that causes interparticle cohesion, and as the moisture content increases further, the particles adhere to the vessel wall due to the adhesive force. In addition, particles with high moisture content (e.g., 90%) showed faster mixing behavior similar to dry particles, as indicated by the Lacey Mixing Index (LMI), while low moisture particles (e.g., 60%) showed the slowest mixing. It is expected that the mixing characteristics of particles depending on the moisture content can be understood and will be useful for the design of horizontal shaft mixers.